Reliability and validity of consumers’ decision making investigation of safe street food purchasing, pilot study in Nakhon Si Thammarat, Thailand - Khongtong, J.; Ab Karim, M. S.; Othman, M.; Bolong, J. B. (International Association of Computer Science and Information Technology, 2015)
Although street food has been the sources of unsafe food for consumption in the world including Thailand, it is interesting that many people are still choosing the food from here. The aim of this study is to investigate consumers’ decision making regarding purchasing safe street food. There is very limited research in this area, therefore this study purposes to develop and test the quality of the instrument. The instrument was developed base on purchasing decision making model, and then tested the validity and reliability of data that collected from 150 pilot respondents by using SEM analysis. The results showed the drawn model was fit with the data. Moreover, the construct reliability (CR > 0.7), convergent validity (AVE > 0.5) and discriminant validity (AVE > r 2 ) were acceptable. As a result, this instrument is capable to be applied in main study and test the research hypotheses. This pilot study can confirm that the instrument is workable and minimize the potential problem that probably occurs according to unclear instrument.